SERUM CALCIUM LEVEL IN NORMAL AND HYPERTENSIVE PREGNANT WOMEN AT WOMEN AND CHILDREN HOSPITAL ABBOTTABAD - Khan, S.P.; Waheed, A.; Khan, J.A; Bano, Aniqa (Journal of Ayub Medical College Abbottabad, 1992)
We have studied ionized serum calcium, total calcium, phosphorus, total protein and albumin in 20 normal pregnant women, 37 moderate and severe pregnancy induced hypertensive women and 9 pregnant women with chronic hypertension. The total serum calcium was significantly reduced in moderate and severe pregnancy induced hypertension and chronic hypertension (P<0.05 and 0.0001 respectively) while ionized calcium was also significantly reduced in pregnancy induced hypertension and chronic hypertension patients as compared to the normotensive pregnant women. (P<0.001 and P<0.0001 respectively). Total protein and albumin was less in hypertensive group as compared to normotensive. Serum phosphate was increased in hypertensive group. It was observed that total calcium and ionized calcium among these hypertensive groups were decreased which support conclusion of other epidemiologic studies of hypertension in non-pregnant patients and pregnant patients that abnormal calcium metabolism contributes to the genesis of hypertensions.